Studi Tingkat Kepuasan Masyarakat Akan Layanan Buy The Service Biskita Trans Pakuan di Kota Bogor Koridor 1 - Mulyawan, Didik Priadi; Murtejo, Tedy; Alimuddin, Alimuddin; Idris, Muhamad Kemal; Sudrajat, Endang (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Customer satisfaction is a feeling of pleasure or disappointment of a customer that comes from a comparison between his impression of the performance or results of a product and his expectations. Performance measurement is a method used to provide an assessment of how much the level of work performance or achievement of predetermined goals and objectives. Buy The Service (BTS) is a service purchase subsidy scheme by the government to the operator (private) in terms providing public transportation services with minimum service standards that must be implemented. Transpakuan has been officially operated since November 2, 2021, serving 4 corridors with a total of 49 fleets. One of them is corridor 1 (Terminal Laladon - Cidangiang). A satisfaction assessment is needed to see whether Biskita Transpakuan Bogor customers are satisfied with the service. The indicators used in the evaluation refer to the Regulation of the Minister of Transportation of the Republic of Indonesia Number 27 of 2015 concerning Amendments to the Regulation of the Minister of Transportation Number 10 of 2012 concerning Minimum Service Standards for Road-Based Mass Transportation. This study aims to determine public satisfaction and the level of performance of Buy The Service (BTS) Biskita Transpakuan Corridor 1 services using the Importance Performance Analysis method & the Customer Satisfaction Index method. The results showed that there are 4 (four) attributes that show consumers are satisfied and must be maintained. There are 6 rated ordinary and 7 (seven) attributes rated excessive. The CSI results show a value of 72.79% in the interval 0.51-0.65, meaning that in general Trans Pakuan bus consumers are in the satisfied category, so that Trans Pakuan's overall performance is considered good. Based on the Importance Satisfaction Analysis method, it shows that the aspects that need to be prioritized are the convenience of cleaning facilities at bus stops, waiting time, information on the arrival time of bus cars and information on disturbances.